Assessing the determinants for the adoption of e-banking services: The case of Dashen bank - Zerihun Ayenew Birbirsa; Ethiopia Teferi; Tesfaye Hailu (Financial Studies, 2019)
The study deals with assessing the determinants for the adoption of e-banking at Dashen Bank selected branches in Addis Ababa, Ethiopia. To meet the objectives of the study, primary data was gathered from selected employees and customers of selected branches of Dashen bank east district in Addis Ababa. These districts include: Bole Medihanialem Branch, Kotebe Branch, Yerer Branch, CMC Branch and Ayat Branch. Hence, Simple random sampling method was employed to draw the sample respondents. Hence out of 388 respondents, 356 responded the questionnaire. The collected data was analyzed using descriptive statistics, correlation and regression analysis. Accordingly, the findings reveal that except perceived risk, which had a negative relationship, perceived ease of use and perceived usefulness had significant and positive relationship with adoption of e-banking. Hence, the study recommended that to enhance e-banking adoption, banks should combine the concepts of perceived ease of use, perceived usefulness, and perceived risk dimensions into e-banking services to increase the level of e-banking adoption and adopt a clear strategy in order to reduce e-banking risk and to improve adoption rate.
Keywords: G21; G29; 330; perceived usefulness; perceived ease of use; perceived risk; e-banking adoption